Advanced semiconductor fundamentals - Pierret, Robert F (Prentice Hall, 2003)
Focus on silicon-based semiconductors—a real-world, market-dominating issue that will appeal to people looking to apply what they are learning. Comprehensive coverage includes treatment of basic semiconductor properties, elements of Quantum Mechanics, energy band theory, equilibrium carrier statistics, recombination-generation processes, and drift/diffusion carrier transport. Practicing engineers and scientists will find this volume helpful, whether it be self-study, reference, or review.